On the distinction of Harmothoe globifera (G.O. Sars, 1873) and some other easily confused polynoids in the NE Atlantic, with the description of a new species of Acanthicolepis Norman in McIntosh, 1900 (Polychaeta, Polynoidae) - Barnich, R.; Fiege, D. (Zootaxa, 2010)
In the Northeast Atlantic several polynoid species have been confused in the past due to similarities in their elytral characters: Harmothoe globifera (G.O.Sars, 1873), Eunoe nodosa (M. Sars, 1861), Eunoe oerstedi Malmgren, 1866, Leucia nivea (M. Sars, 1863), and Acanthicolepis zibrowii n. sp., a new species from deep cold-water corals. The five species are redescribed and figured based on type and additional material. An identification key allowing also the identification of juveniles and anterior fragments and a synoptic table listing the major distinguishing characters of the species covered are provided
Polychaeta database